Cytotoxic effects of dental calculus particles and freeze‐dried Aggregatibacter actinomycetemcomitans and Fusobacterium nucleatum on HSC‐2 oral epithelial cells and THP‐1 macrophages. Issue 6 (6th October 2021) - Ziauddin, S.M.; Alam, Mohammad Ibtehaz; Mae, Megumi; Oohira, Masayuki; Higuchi, Kanako; Yamashita, Yasunori; Ozaki, Yukio; Yoshimura, Atsutoshi
Abstract: Background: Periodontitis is an inflammatory disease initiated by dental deposits. Microorganisms in the dental biofilm induce cell death in epithelial cells, contributing to the breakdown of epithelial barrier function. Recently, dental calculus has also been implicated in pyroptotic cell death in oral epithelium. We analyzed the cytotoxic effects of dental calculus and freeze‐dried periodontopathic bacteria on oral epithelial cells and macrophages. Methods: HSC‐2 (human oral squamous carcinoma cells) and phorbol 12‐myristate 13‐acetate‒differentiated THP‐1 macrophages were exposed to dental calculus or one of two species of freeze‐dried bacterium, Aggregatibacter actinomycetemcomitans and Fusobacterium nucleatum . Following incubation for 24 hours, we measured cytotoxicity via lactate dehydrogenase release. Cells were then incubated with glyburide, an NLRP3 inflammasome inhibitor, to assess the potential role of pyroptosis. We also conducted a permeability assay to analyze the effects on epithelial barrier function. Results: Dental calculus induced dose‐dependent cell death in HSC‐2 cells, whereas cell death induced by freeze‐dried bacteria was insignificant. Conversely, freeze‐dried bacteria induced more cell death than dental calculus in THP‐1 macrophages. Cell death induced by dental calculus but not by freeze‐dried bacteria was inhibited by glyburide, indicating that these are different types of cell death. In the permeability assays, dental calculus but not freeze‐dried bacteria attenuated the barrier function of HSC‐2 cell monolayers. Conclusion: Due to the low sensitivity of HSC‐2 cells to microbial cytotoxicity, dental calculus had stronger cytotoxic effects on HSC‐2 cell monolayers than freeze‐dried A. actinomycetemcomitans and F. nucleatum, suggesting that it plays a critical role in the breakdown of crevicular/pocket epithelium integrity.